Vascular Effects of the Polyphenolic Nutraceutical Supplement Taurisolo(®): Focus on the Protection of the Endothelial Function - Martelli, Alma (Nutrients, 2021)
Preservation of vascular endothelium integrity and functionality represents an unmet medical need. Indeed, endothelial dysfunction leads to decreased nitric oxide biosynthesis, which is prodromic of hypertension and hypercoagulability. In this panorama, the nutraceutical supplement Taurisolo(®), a polyphenolic extract from Aglianico cultivar grape, rich in catechin and procyanidins, was evaluated as a vasoprotective, vasorelaxing, anti-hypertensive and anti-coagulant agent in: cell lines, isolated vessels, in vivo models of chronic hypertension and hypercoagulability, and in clinical tests of endothelial reactivity. Taurisolo(®) demonstrated to fully protect vascular cell viability from oxidative stimulus at 100 µg/mL and evoke vasorelaxing effects (Emax = 80.6% ± 1.9 and pEC50 = 1.19 ± 0.03) by activation of the Sirtuins-AMPK-pathway. Moreover, Taurisolo(®), chronically administered at 20 mg/Kg/die in in vivo experiments, inhibited the onset of cardiac hypertrophy (heart weight/rat weight = 3.96 ± 0.09 vs. 4.30 ± 0.03), hypercoagulability (decrease of fibrinogen vs. control: p < 0.01) and hypertension (mean of Psys: 200 ± 2 vs. control 234 ± 2 mmHg) and improved endothelial function (Emax = 88.9% ± 1.5 vs. control 59.6% ± 3.6; flow-mediated dilation in healthy volunteers after 400 mg twice daily for 8 weeks vs. baseline: p = 0.019). In conclusion, Taurisolo(®) preserves the vascular function against ox-inflamm-ageing process and the consequent cardiovascular accidents.